Teologi Kontekstual Kutuk dan Berkat dari Pemahaman Warga Jemaat - Olivia Joan Warisal; Agustinus M.L Batlajery; Steve G.C Gaspersz (Program Pascasarjana UKIM, 2023)
The concepts of curses and blessings are discussed not only in the Bible but also in the lives of church members today. Congregation members in Nalahia (of the Protestant Church in the Moluccas), as a research locus, always associate the concept of curses and blessings with traditional practices and daily life. Pilgrims who carry out their customary obligations will be blessed, while those who are negligent will be cursed. This study aims to reconstruct contextual theology regarding the understanding of curses and blessings from church members. Using qualitative research methods, data were collected from interviews with congregation members and analyzed dialectically with various contextual theological literature. The results of this study indicate that members of the local congregation who are still influenced by multi-layered cultural traditions understand their relationship with God and their ancestors in layers. Expressions of faith in a cultural context open reflections on the meaning of God's creations in the reality of human life, including in cultural practices. Contextual theology does not fall from the sky but is always dialectical with the context that produces the theology, including the cultural context.